Liposomes containing phosphorylated tau peptides for inducing sustained immune responses - PFEIFER, ANDREA; GAPPEN, WOLFGANG; MUHS, ANDREAS (2024)
Methods for inducing a sustained immune response against phosphorylated Tau in a human are described. The method comprises administering to the subject an effective amount of a liposome comprising a toll-like receptor 4 agonist, a helper T cell epitope, a lipidated CpG oligonucleotide, and a Tau phosphopeptide presented on the surface of the liposome to thereby obtain a sustained immune response. 描述了用于在人中诱导针对磷酸化Tau的持续免疫反应的方法。该方法包括向受试者施用有效量的包括toll样受体4激动剂、辅助性T细胞表位、脂质化CpG寡核苷酸、和呈递在脂质体的表面上的Tau磷酸肽的脂质体，以由此获得持续免疫反应。